Starter Experiment Approach terhadap Kemampuan Pemahaman Konsep Mahasiswa Calon Guru - Rudi Haryadi; Heni Pujiastuti (Universitas Muhammadiyah Enrekang, 2021)
The purpose of this study is to improve the understanding of the concept of prospective teachers in applied physics courses by applying the Starter Experiment Approach when the lectures take place. Starter Experiment Approach is an approach used as a tool for students to practice the skills of observation, because in this approach are consecutively trained to formulate problems, formulate temporary answers from the problem formulated (hypothesis), designing experiments, experimenting, and reporting results trial. The research method used quasi experiment with Pretest-Posttest Control Group Design. Research sample is divided into two classes, namely experiment class and control class. The experimental class uses learning with the Starter Experiment Approach learning model while the control class uses the conventional learning model. Based on the result of research, it is found that the average of N-gain understanding of student concept using learning model starter experiment approach is 0,74, mean of N-gain understanding of student concept with conventional learning equal to 0,23. These data suggest that the understanding of physics concepts using the Starter Experiment Approach learning model is higher than the understanding of physics concepts using conventional learning models. Then based on data analysis show that tcount = 14,196 and ttable = 2.01 (5% significance level). This means tcount> ttable, so it can be interpreted that there is a significant difference in the ability of student concept between student groups applying Starter Experiment Approach (SEA) and group of students using conventional learning model. So the application of Starter Experiment Approach (SEA) has a positive effect on the ability to understand the concept of prospective teachers in applied physics courses.